Maternal socioeconomic factors and adverse perinatal outcomes in two birth cohorts, 1997/98 and 2010, in São Luís, Brazil - Nádia Carenina Nunes Cavalcante; Vanda Maria Ferreira Simões; Marizélia Rodrigues Costa Ribeiro; Fernando Lamy-Filho; Marco Antonio Barbieri; Heloisa Bettiol; Antônio Augusto Moura da Silva
ABSTRACT: Several studies have identified social inequalities in low birth weight (LBW), preterm birth (PTB), and intrauterine growth restriction (IUGR), which, in recent years, have diminished or disappeared in certain locations. Objectives: Estimate the LBW, PTB, and IUGR rates in São Luís, Maranhão, Brazil, in 2010, and check for associations between socioeconomic factors and these indicators. Methods: This study is based on a birth cohort performed in São Luís. It included 5,051 singleton hospital births in 2010. The chi-square test was used for proportion comparisons, while simple and multiple Poisson regression models with robust error variance were used to estimate relative risks. Results: LBW, PTB and IUGR rates were 7.5, 12.2, and 10.3% respectively. LBW was higher in low-income families, while PTB and IUGR were not associated with socioeconomic factors. Conclusion: The absence or weak association of these indicators with social inequality point to improvements in health care and/or in social conditions in São Luís.